Assessment of the effects of production system development projects: Case study of Lytkarino Optical Glass Factory - M. A. Abdulkadyrov; A. N. Ignatov; N. N. Kulikova; E. S. Mityakov (Российский технологический журнал, 2023)
Objectives. Effective import substitution can be achieved only through the creation and use of efficient domestic production capacities. The aim of this study is to develop and justify a method for the integrated assessment of the effects of projects aimed at the introduction of new equipment, including import substitution projects.Methods. The research was based on systemic and dialectical approaches, as well as systemic, comparative, economic and mathematical methods, and statistical analysis.Results. The paper proposes a method for the integrated assessment of production system development projects. In order to obtain a synthetic assessment, a system of indicators was developed to study the effects of production system development projects, i.e., projects for the introduction of new equipment. The effects of the introduction of new equipment can be divided into internal and external: potential development, socioeconomic, import independence, public, and environmental. The indicators are not current values, but changes in dynamics. A comprehensive consideration of the effects allows the existing criteria for decision-making to be expanded when implementing projects to develop the production system. It also allows the impact on both the enterprise and society to be assessed. The authors define both the quantitative and qualitative indicators for each group of effects. On the basis of the author’s system of indicators, a methodology for comparative comparison of indicators using normalized indices was developed and the calculation of a generalized indicator substantiated. The proposed system of indicators was successfully tested at the Lytkarino Optical Glass Factory science-intensive enterprise when assessing a new domestic device for the development of the production system.Conclusions. The results of the approved method for integrated assessment enabled the use of diverse indicators for the quantitative and qualitative assessment of the effects of the introduction of science-intensive projects. This included projects for import substitution of machinery and equipment. A combination of various effects will be relevant to any socioeconomic system, so the proposed integrated assessment method for evaluating the effects is universal to a certain extent. It can thus be adapted for scientific, technical and technological projects on import substitution of any industrial enterprise.